2015
DOI: 10.14260/jemds/2015/597
|View full text |Cite
|
Sign up to set email alerts
|

Upper Lip Bite Test : A Novel Test of Predicting Difficulty in Intubation

Abstract: BACKGROUND:Although there are many preoperative tests to predict difficult airway, they are far from being ideal i. e. easy to perform, highly sensitive and specific, having high positive predictive value with few false positive predictions. AIMS: to elucidate the role of upper lip bite test (ULBT) with other prevailing tests, hyomental/thyrosternal distance ((HMD/ TSD), and mandible length (ML) in predicting difficulty in endotracheal intubation. MATERIAL AND METHOD: 300 patients meeting inclusion criteria, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…). After detailed assessment, we included 133 studies (127 cohort type and six case–control) involving 844,206 participants . Of the 133 studies, there were six for the Mallampati test, 105 for the modified Mallampati test, six for Wilson risk score, 52 for thyromental distance, 18 for sternomental distance, 34 for the mouth opening test and 30 for the upper lip bite test.…”
Section: Resultsmentioning
confidence: 99%
“…Observational studies reported comparative findings for facial and jaw features and anatomical measurement for difficult versus nondifficult airway patients as well as sensitivity, specificity, positive predictive, negative predictive, and accuracy values for difficult laryngoscopy and intubation. Findings for facial and jaw features, 7–11,13,14,18,27,33,38–40,42,43,45–47,49,51–54,57,58,64,68,123–159 anatomical measurements, 7–11,13–15,18,22,23,27–30,33,35,37–40,45–47,49,51–54,57,58,60, 64,65,68,70,123–132,134–154,156,158–203 and ultrasound anatomical measurements 69,139,162,170,194,196,203–213 were shown to have very high predictive and comparative variability, with sensitivity, specificity, and significance values ranging from low to very high across all patient measures (Category B2-E evidence). No single characteristic was identified as consistently being more predictive than another, and multivariate measures intended to predict difficult airways were too few and diverse among the studies to determine a common set of predictors.…”
Section: Guidelinesmentioning
confidence: 99%
“…One hundred seventy-eight papers used prospective design, twelve used retrospective design, eighteen papers used case–control design. Sixty-nine papers used blinded experiment [ 15 , 20 , 25 , 29 – 31 , 44 , 50 , 57 , 60 , 61 , 63 , 71 , 75 , 77 , 86 , 90 , 91 , 95 , 98 , 102 , 112 , 115 , 116 , 123 125 , 127 – 129 , 139 , 140 , 143 , 147 , 152 , 159 – 161 , 169 , 171 174 , 179 183 , 185 , 186 , 188 – 192 , 196 , 201 , 204 , 208 , 209 , 211 , 218 , 228 230 , 234 ]. Twenty-four specifically selected obese populations for research [ 36 , 39 , 40 , 43 , 59 , 61 , 65 , 70 , 86 , 99 , 106 , 109 , 121 ,…”
Section: Resultsmentioning
confidence: 99%
“…Almost all studies indicated that difficult tracheal intubation assessment was performed before surgery. Only 69 articles explicitly used blinded methods [ 15 , 20 , 25 , 29 – 31 , 44 , 50 , 57 , 60 , 61 , 63 , 71 , 75 , 77 , 86 , 90 , 91 , 95 , 98 , 102 , 112 , 115 , 116 , 123 125 , 127 – 129 , 139 , 140 , 143 , 147 , 152 , 159 – 161 , 169 , 171 174 , 179 183 , 185 , 186 , 188 – 192 , 196 , 201 , 204 , 208 , 209 , 211 , 218 , 228 230 , 234 ]. When assessing the risk of bias in 227 studies using the QUADAS-2 tool, 27 studies showed problems with patient selection, 10 studies showed problems with index testing, 49 studies showed problems with reference standards, and 33 studies showed problems with procedures and timing.…”
Section: Resultsmentioning
confidence: 99%